Characterisation of haematological profiles and whole blood relative gene expression levels in Holstein-Friesian and Jersey bull calves undergoing gradual weaning. (20th November 2015) - Johnston, D.; Kenny, D. A.; Kelly, A. K.; McCabe, M. S.; McGee, M.; Waters, S. M.; Earley, B.
Abstract : Haematological profiles indicate the health status of an animal and can be used to identify sub-clinical stress responses. The objectives of the study were to examine (i) the effect of breed and plane of nutrition, on haematological profiles of artificially reared Holstein-Friesian and Jersey bull calves in response to gradual weaning, and (ii) the effect of breed on immune response genes in bovine whole blood using real-time quantitative PCR. Holstein-Friesian and Jersey bull calves were group housed indoors and individually fed using an automatic feeder. They were allocated to a high, medium or low plane of nutrition, based on milk replacer (MR) and concentrate. The nutrition treatments were calculated using National Research Council guidelines in order to achieve a high, medium or low growth rate for each respective breed. During the weaning phase MR was gradually reduced over a 14-day (d) period (d −13 to d 0). Calves were blood sampled on d −14, −6, −3, 0, 1, 3, 8 and 14 relative to weaning (d 0) for subsequent haematological analysis. On d −14, 1 and 8, a subset of eight Holstein-Friesian calves randomly selected from the medium nutrition treatment and eight Jersey calves randomly selected from the high nutrition treatment, were blood sampled for gene expression profiling, targeting biomarkers of weaning stress. These two treatment groups were chosen to examine the effect of breed on expression of the genes of interest, as energy intake and animal performance were similar. There was no effect of breed×plane of nutrition interaction nor effect of plane of nutrition on any variable measured ( P >0.05). Gradual weaning produced differential biological responses in the two breeds evidenced by breed×time interactions for lymphocyte, monocyte and red blood cell number, plasma haemoglobin and haptoglobin concentrations ( P <0.05). The typical stress response consisting of neutrophilia and lymphopaenia was not observed for any treatment. An immune response to gradual weaning was observed as the relative gene expression level of the pro-apoptotic gene, Fas, increased on d 1 relative to d −14 ( P <0.05). Relative gene expression levels were greater in Jersey calves compared with Holstein-Friesian for the pro-inflammatory cytokine CXCL8 ( P =0.05) and the glucocorticoid receptor, GRα ( P <0.05). The increased levels of these transcripts suggest that Jersey calves may have a more sensitive immune system compared with Holstein-Friesian.